2003
DOI: 10.1128/jb.185.24.7120-7128.2003
|View full text |Cite
|
Sign up to set email alerts
|

PropaneMonooxygenase and NAD + -Dependent Secondary AlcoholDehydrogenase in Propane Metabolism by Gordonia sp.StrainTY-5

Abstract: A new isolate, Gordonia sp. strain TY-5, is capable of growth on propane and n-alkanes with C 13 to C 22 carbon chains as the sole source of carbon. In whole-cell reactions, significant propane oxidation to 2-propanol was detected. A gene cluster designated prmABCD, which encodes the components of a putative dinucleariron-containing multicomponent monooxygenase, including the large and small subunits of the hydroxylase, an NADH-dependent acceptor oxidoreductase, and a coupling protein, was cloned and sequenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 67 publications
3
121
0
Order By: Relevance
“…TY-6 and Pseudonocardia sp. TY-7 have suggested that they are similar to sBMO in that they are specific for short-chain C 2 -C 6 alkanes but poorly suited for methane oxidation (Kotani et al, 2003(Kotani et al, , 2006.…”
Section: Substrate Specificitymentioning
confidence: 99%
“…TY-6 and Pseudonocardia sp. TY-7 have suggested that they are similar to sBMO in that they are specific for short-chain C 2 -C 6 alkanes but poorly suited for methane oxidation (Kotani et al, 2003(Kotani et al, , 2006.…”
Section: Substrate Specificitymentioning
confidence: 99%
“…Cloning and DNA sequence analysis of the fragment expressed by strain ENV425 following growth on propane identified the gene as a homologue of the PMO present in Gordonia sp. Strain TY-5 (Kotani et al, 2003) and its putative homologues in Rhodococcus sp. Strain RHA1 (McLeod et al, 2006) and Mycobacterium smegmatis MC2 155 (Genbank number CP000480) ( Figure 22).…”
Section: Results and Discussion: Molecular Analysis Of Env425mentioning
confidence: 99%
“…Gaseous n-alkanes ranging from C 2 to C 5 are recognized as components of non-methane hydrocarbons, and their increased concentrations in the atmosphere threaten to destabilize ecosystems through a variety of mechanisms [118,119]. Although these gases are produced as natural intermediates of bacterial, plant, and mammalian metabolism, the main sources of pollution is represented by natural oil seepages and oil spills [20,119].…”
Section: Sdimo -Short-alkanes Oxidizing Monooxygenasesmentioning
confidence: 99%
“…Although these gases are produced as natural intermediates of bacterial, plant, and mammalian metabolism, the main sources of pollution is represented by natural oil seepages and oil spills [20,119]. From a biotechnological perspective, gaseous alkanes are inexpensive carbon sources for microbial and increases the rates of substrate turnover [25,122,123].…”
Section: Sdimo -Short-alkanes Oxidizing Monooxygenasesmentioning
confidence: 99%
See 1 more Smart Citation